Perlindungan Hukum Pembeli Perumahan Subsidi - Ramadhani, Sidney Reviano (UM Purwokerto Press, 2024)
The study investigates policies and law related to the protection of law for the purchase of subsidized housing. The study focuses on the subsidized housing biding agreement and the legal protection applied to the home buyer facing the developer. Research results show that legal protection for subsidized housing buyers still has weaknesses. Therefore, this study recommends several measures to improve legal protection, such as raising consumer awareness of their right and increasing transparency in biding sales agreements. Overall, this research is expected to help create better policies and law to protect consumer right in the sale of subsidized houses.